Psychoeducation of bipolar disorder patients and their relatives - Michel Bourin (Archives of Depression and Anxiety - Peertechz Publications, 2018)
Until recently, there was the belief that people with bipolar disorder were not fi t to be treated with psychological therapies, which has been widely denied in recent years. While it is true that the effects of therapy are not immediate, psychoeducation also demonstrates its long-term benefi ts in people with bipolar disorder who have attended these therapies on an ongoing basis. Psychoeducation is a very important topic often neglected, but it is a very important task of physicians to well explain to patients and their families what is the illness and to prevent depression or manic and hypomanic episodes.  Psychoeducation for patients with bipolar disorder aims to overcome the therapeutic challenges posed by the disease by making patients actors in their care [1].